The Bacidia coprodes group (Ramalinaceae, Lecanoromycetes, Ascomycota), with special reference to the species in Europe and North America - Ekman, Stefan (Phytotaxa, 2014)
This paper aims to clarify taxonomy and nomenclature of the lichen Bacidia coprodes and its closest relatives in Europe and North America. Bacidia coprodes as treated in recent works was found to consist of three distinct species in Europe and North America, the correct names of which are B. coprodes (s. str.), B. notarisiana, and B. granosa. In addition, a fourth species, B. inornata (Nyl.) Blomb. & Forssell, was found to be closely related to this group of lichens and is also treated here. The four species can be separated by apothecial and pycnidial pigmentation as well as conidium shape and size. They are closely related to species currently treated in Bacidia, Toninia, or Arthrosporum. Six basionyms, viz. Bilimbia coprodes, Patellaria salevensis, Bilimbia subtrachona, Lecidea chytrina, L. chytrina var. hormospora, and L. inornata, are lectotypified. Detailed descriptions and a determination key are provided.